2011
DOI: 10.1111/j.1745-4514.2010.00514.x
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibitory Actions of Houttuynia Cordata Aqueous Extract on Dengue Virus and Dengue-Infected Cells

Abstract: The antiviral activities of Houttuynia cordata (H. cordata) aqueous extract against dengue virus serotype 2 (DEN‐2), strain 16681, were evaluated in this study. The results showed that pre‐ and post‐incubation of H. cordata extract (10–100 µg/mL) with HepG2 cells significantly reduced intracellular DEN‐2 RNA production correlating with the decrease in dengue protein expression. In the direct blocking mode, the extract bound with DEN‐2 and strongly inhibited the intracellular viral RNA replication with an effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 26 publications
1
30
0
1
Order By: Relevance
“…Highperformance liquid chromatography of the aqueous extract revealed that hyperoside (compound 39) (Figure 6) is the major component of the extract, suggesting that this flavonoid plays an important role in DENV-2 inhibition. The aqueous extract had no toxic effects on human blood cells [53]. Figure 7 suggest that ajugasterone C (compound 42) is equipotent to 2´-Cmethylcytidine (positive control), with a better SI.…”
Section: Indirect Inhibitory Activities Of Compounds and Extracts Agamentioning
confidence: 96%
“…Highperformance liquid chromatography of the aqueous extract revealed that hyperoside (compound 39) (Figure 6) is the major component of the extract, suggesting that this flavonoid plays an important role in DENV-2 inhibition. The aqueous extract had no toxic effects on human blood cells [53]. Figure 7 suggest that ajugasterone C (compound 42) is equipotent to 2´-Cmethylcytidine (positive control), with a better SI.…”
Section: Indirect Inhibitory Activities Of Compounds and Extracts Agamentioning
confidence: 96%
“…Infection with one DENV serotype produces only specific antibody against that serotype. When antibody from the first infection is neutralized, secondary infections by other serotypes can cause more serious infection (Leardkamolkarn et al, 2012). Although DENV-2 is known to be more lethal than other serotypes (Goel et al, 2004), some studies have revealed that primary infection with DENV-1 or DENV-3 always results in more dangerous disease than infection with the other serotypes (Guzman and Isturiz, 2010;Tang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Dengue was seen a 30-fold upsurge worldwide between 1960 and 2010 due to increased population growth rate, global warming, unplanned urbanization, inefficient mosquito control, frequent air travel, and lack of health care facilities (2)(3)(4)(5). Two and a half billion people reside in dengue-endemic regions and 400 million infections roughly occur per year, with a mortality rate surpassing 5% -20% in some areas (6,7). Dengue infection affects more than 100 countries, including European countries and the United States (USA) (7).…”
Section: Introductionmentioning
confidence: 99%
“…Nonstructural proteins are responsible for the replication of viral genome and evasion from host immunity. Many antiviral compounds have been reported to inhibit DENV replication in vitro and in vivo (6,11,12). However, no approved antiviral drug is yet available for the treatment of DENV infectious disease.…”
Section: Introductionmentioning
confidence: 99%